Perbadingan Hasil Pemeriksaan pH dan Leukosit Menggunakan Urin Segar dan Urin Tunda 2 Jam pada Pasien Infeksi Saluran Kemih (ISK) dengan Metode Carik Celup - Natalia, Anjela Stefanie; Abadi, Moh. Fairuz; Subhaktiyasa, Putu Gede (Jaringan Laboratorium Medis, 2025)
Urinary Tract Infection (UTI) is one of the most prevalent diseases that requires rapid and accurate laboratory diagnosis. Urine examination using dipstick methods serves as a practical diagnostic alternative. However, the stability of urine specimens subjected to delayed examination needs further evaluation, particularly regarding pH and leukocyte parameters. This study aimed to determine the differences in urine pH and leukocyte results between fresh urine and urine stored for 2 hours at room temperature using the dipstick method in UTI patients. This experimental study employed a quantitative approach. A total of 30 urine samples were collected from UTI patients at RSAD Tk. II Udayana. Each sample was analyzed under two conditions: immediately (fresh urine) and after 2 hours of storage at room temperature (delayed urine), yielding a total of 60 measurements. The results showed an increase in the median urine pH from 6.0 to 6.5 and a decrease in leukocyte count from a median of 125 to 70 after 2 hours of storage at room temperature, with statistically significant differences (p < 0.05). These findings indicate that delaying urine examination for 2 hours can affect pH and leukocyte values, potentially leading to inaccurate diagnostic interpretation. Therefore, urine chemical examination should be performed within one hour after collection or stored at 2–8 °C to maintain result accuracy.